Some of the biochemistry properties of xylanase synthesized from Aspergillus niger van Tieghem var niger - Nguyen, Quynh Uyen (NXB Nông Nghiệp, 2011)
Xylanase synthesized from filamentous fungi has been shown to have many important applications in industries. In this article, the optimized growing conditions as well as some of the biochemistry characteristics xylanase of Aspergillus niger van Tieghem varnigerhas been studied primarily. The optimized growing conditions of this strainwere determined as follows: bran/husk (1:1, w/w) medium was used, the temperature was 30 oC and the growing time was 7 days. Theoptimized pH of this enzyme was 5 and its optimized temperature was 50 oC. This enzyme is not thermo-stable. In addition, the xylanase of Aspergillus niger van Tieghem varniger was primarily purified via gel filtration and after this process its purity was increased 2.1 times.